Effects of combined Adeli suit and neurodevelopmental treatment in children with spastic cerebral palsy with gross motor function classification system levels I and II - Mi-Ra Kim, MS, PT; Byoung-Hee Lee, PhD; Dae-Sung Park, PT, PhD (World Scientific Publishing, 2016)
Background: Children with cerebral palsy (CP) exhibit diverse gait patterns depending on their neurological deficits and musculoskeletal problems. The Adeli suit treatment (AST) has been proposed as an intensive exercise protocol in the management of CP. Objectives: The aim of this study was to compare the effects of a 6-week programme of combined AST and neurodevelopment treatment (NDT) with those of NDT alone on Gross Motor Function Measure (GMFM), balance, and gait in children with CP. Methods: Twenty children with CP of Gross Motor Function Classification System levels I and II were randomly assigned to one of the following two groups: (1) NDT or (2) AST/NDT. The participants were assessed using the GMFM, Pediatric Balance Scale (PBS), Timed Up and Go (TUG) test, and spatiotemporal gait parameters. Results: The GMFM, PBS, and TUG test for both groups showed a statistically significant increase (p < 0.05). Three children were excluded. Compared to the NDT group (n = 9), the AST/NDT group (n = 8) demonstrated a significant increase in spatiotemporal gait parameters (p < 0.05). Conclusion: These results provide evidence for the greater effectiveness of combined AST/NDT than NDT alone in improving spatiotemporal gait parameters but not GMFM, PBS, and TUG test.